CRIMINAL LAW POLICY IN OVERCOMING INFRINGEMENT OF COPYRIGHT - Retnowat, Anny; Christiani, Theresia Anita; Kastowo, Chryssantus (International Journal of Psychosocial Rehabilitation, 2020)
The Indonesia Copyright Act states that criminal acts of copyright constitute a complaint of infringement. Legal issues are, first, whether the development of copyright provisions has provided legal protection to the creator. Second, how the policy of criminal law is to provide legal protection to the creator. This research is based on normative research methods. The results showed that, first, the effectiveness of copyright provisions in the provision of legal protection to creators has not yet been shown to be active. Although the attack usually empowers law enforcement officials to take direct action against copyright infringement. With the new provisions, the copyright owner must actively complain that there is a violation of its creation without complaint; the nature appears to be unprotected by the law. Second, the criminal law policy of providing legal protection to the creator at the stage (legislative policy) appears to lack the ability to be able to include social symptoms in legal rules by modifying the infringement of copyright is an infringement of the complaint. On the other hand, at the application stage (policy justice), law enforcement officials appear to be passive in their response, and the execution stage (executive policy) of the statutory regulation is formed by the hope that they can be consciously accepted and obeyed by all people without exception.